2022
DOI: 10.1021/acsnano.2c00955
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Waste Product Captures Carbon Dioxide in Nanometer Pores

Abstract: Plastic waste (PW) and increasing atmospheric carbon dioxide (CO 2 ) levels are among the top environmental concerns presently facing humankind. With an ambitious 2050 zero-CO 2 emissions goal, there is a demand for economical CO 2 capture routes. Here we show that the thermal treatment of PW in the presence of potassium acetate yields an effective carbon sorbent with pores width of 0.7−1.4 nm for CO 2 capture. The PW to carbon sorbent process works with single or mixed streams of polyolefin plastics. The CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…On the other hand, the backbone of charring plastics (including PET, PVC, and PS) experiences cyclization, aromatization, and crosslinking instead of being decomposed into small molecular gases, and then carbon material frames will be constructed. This is beneficial for the production of carbon nanosheets and porous carbon but is detrimental to the formation of smooth carbon spheres (Algozeeb et al 2022 ; Sawant et al 2013 ). Most waste plastics are mixed plastics and consist of additives and contaminants, so the influences of the three factors should be critical for the carbonization and reutilization of plastics, and deserve more attention in future research.…”
Section: Impacts Of Plastic Types On the Plastics Carbonizationmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the backbone of charring plastics (including PET, PVC, and PS) experiences cyclization, aromatization, and crosslinking instead of being decomposed into small molecular gases, and then carbon material frames will be constructed. This is beneficial for the production of carbon nanosheets and porous carbon but is detrimental to the formation of smooth carbon spheres (Algozeeb et al 2022 ; Sawant et al 2013 ). Most waste plastics are mixed plastics and consist of additives and contaminants, so the influences of the three factors should be critical for the carbonization and reutilization of plastics, and deserve more attention in future research.…”
Section: Impacts Of Plastic Types On the Plastics Carbonizationmentioning
confidence: 99%
“…Due to its high specific surface area, low cost, adjustable pore structure, and good electrical conductivity, porous carbon has been widely applied in CO 2 capture (Algozeeb et al 2022 ; Song et al 2022 ), solar steam evaporation (Zhang et al 2019a ), supercapacitor (Cheng et al 2015 ; Ma et al 2020b ; Min et al 2019 ; Zhang et al 2021a ), and battery (Min et al 2020 ). Thus, the carbonization of waste plastics to porous carbons is beneficial for wide applications.…”
Section: Morphology Control Of Carbonaceous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Name., 2022, 00, 1-3 This journal is © The Royal Society of Chemistry 20xxPlease do not adjust margins Please do not adjust margins demonstrated that pyrolysis of HDPE, LDPE and PP in the presence of potassium acetate salt could yield porous carbons with pore widths of 0.7-1.4 nm for CO 2 capture, instead of valueless carbon char 72. Single or mixed polyolefin feedstock could afford sorbents with CO 2 capacities of 3.80 mmol g -1 (1 bar CO 2 , 25 o C), and could be easily regenerated at approximately 75 o C.…”
mentioning
confidence: 99%